Analysis of Hierarchical Routing Models - Hailan, Ahmad M. (Iraqi Journal of Science, 2022)
In this study, flow-based routing model is investigated. The aim of this study is to increase scalability of flow control, routing and network resources solutions, as well as to improve Quality of Service and performance of the whole system. A method of hierarchical routing is proposed. The goal coordination method alsoused in this paper. Two routing models (model with quadratic objective function and model with traffic engineering) were fully analyzed. The basic functions of the hierarchical routing model levels based on goal coordination method were addressed Both models’ convergence is also explained. The dependence of the coordination iterations number on the packet flow rates for both models is graphically shown. The results shows that the method of efficiency is improved by increasing the link metric. Applying the proposed method can improve the scalability of routing decisions in the telecommunication network. Additionally, the proposed method can reduce the number of iterations in the implementation of hierarchical routing, and reduce the service traffic volume in the network.